Unlocking the Medicinal Treasure of Cinnamomum Tamala (Bay Leaf): A Comprehensive Review of its Therapeutic and Pharmaceutical Potential - Vaishnav, Som; Shahi, Sanyogita (Journal of Neonatal Surgery, 2025)
Cinnamomum tamala, known as bay leaf, is a medicinal plant with a rich history in traditional medicine and culinary applications. This review highlights its diverse pharmacological properties, including antioxidant, anti-inflammatory, antimicrobial, antidiabetic, and anticancer effects, stemming from its abundant phytochemicals, such as essential oils (cinnamaldehyde, eugenol, linalool) and flavonoids (quercetin, kaempferol). These bioactive compounds contribute to its protective actions against oxidative stress, inflammatory conditions, infections, and metabolic disorders. While preclinical studies show promising efficacy, the widespread pharmaceutical use of Cinnamomum tamala is currently limited by a lack of extensive clinical trials, bioavailability challenges, and the absence of standardised formulations. Future research should prioritise optimising extraction methods, enhancing bioavailability through advanced drug delivery, and conducting rigorous clinical studies to validate its therapeutic potential. Exploring synergistic effects with conventional drugs may further amplify its pharmacological benefits. This review comprehensively analyses the therapeutic and pharmaceutical significance of Cinnamomum tamala, summarising its bioactive components, mechanisms of action, and potential in modern medicine. By addressing current obstacles and outlining future directions, this study aims to contribute to the growing integration of natural medicinal agents into modern therapeutics.